Age- and Gender-Related Changes in Physical Function in Community-Dwelling Brazilian Adults Aged 50 to 102 Years. Issue 2 (April 2021) - Coelho-Junior, Hélio J.; Uchida, Marco C.; Gonçalves, Ivan O.; Calvani, Riccardo; Rodrigues, Bruno; Picca, Anna; Onder, Graziano; Landi, Francesco; Bernabei, Roberto; Marzetti, Emanuele
Abstract : Background and Purpose: Cutoff points for physical function tests are commonly used in clinical practice for the evaluation, monitoring, and treatment of older adults. Previous studies have shown that, while age-related patterns of muscle strength change are similar between ethnic groups, strength values differ significantly independent of age. Whether the same applies to other physical function tests is presently unclear. This study investigated age- and gender-related changes of performance on a battery of physical function tests in Brazilian community dwellers. Methods: The study followed a cross-sectional design. Participants were community-dwelling adults. Candidates were considered eligible if they were 18 years or older, lived independently, and possessed sufficient physical and cognitive abilities to perform all of the measurements required by the protocol. Physical function tests included isometric handgrip (IHG), 5 times sit-to-stand (5×STS) test, Timed Up and Go, 1-leg stance, and walking speed (WS) at usual and fast pace. Results: Two-thousand eight-hundred and four people were enrolled. Mean age was 68.0 (7.0) years (range 50-102 years), and 2262 (80.7%) were women. Men displayed better IHG and balance, while women showed higher performance on the 5×STS and WS tests. A gender-specific pattern of decline in physical performance was observed. Specifically, women showed a linear age-dependent decline in all tests. In men, only in the IHG, 1-leg stance, and WS test at a fast pace was there a linear decline with age. In both genders, the lowest mean values of physical function tests were higher than the proposed cutoffs for sarcopenia. Discussion and Conclusions: Our findings indicate that the performance on different physical function tests decreases with advancing age in Brazilian adults, following a gender-specific pattern. In none of the tests did the lowest mean values reach the cutoffs for sarcopenia. This suggests that region-specific cutoffs might be necessary to identify older people at risk of adverse events. Abstract : Supplemental Digital Content is Available in the Text.